2003
DOI: 10.1116/1.1585069
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in Mn- and Co-implanted ZnO nanorods

Abstract: ZnO nanorods with diameters of 15-30 nm were grown on Ag-coated Si substrates by catalyst-driven molecular beam epitaxy and then implanted with Mn ϩ or Co ϩ ions to doses of 1 -5ϫ10 16 cm Ϫ2 . After subsequent annealing at 700°C for 5 min, the structural properties of the nanorods were unaffected, but they exhibited ferromagnetism that persisted to temperatures of 225-300 K. The coercive fields were р100 Oe even at 10 K. The results are similar to those obtained for implantation of Mn ϩ or Co ϩ ions in bulk si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…Furthermore, even if Co precipitations account for the origin of the observed ferromagnetism, the diameter of which should be above 5 nm, because Co particles smaller than that size are superparamagnetic at room temperature. 19 In any case, the appearance of Co clusters with diameter larger than 5 nm is beyond belief under the aforementioned growth process. Further studies such as magneto-optical spectrum 20 measurement are planned to obtain more convincing evidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even if Co precipitations account for the origin of the observed ferromagnetism, the diameter of which should be above 5 nm, because Co particles smaller than that size are superparamagnetic at room temperature. 19 In any case, the appearance of Co clusters with diameter larger than 5 nm is beyond belief under the aforementioned growth process. Further studies such as magneto-optical spectrum 20 measurement are planned to obtain more convincing evidence.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO is transparent to visible light, and has a higher TM solubility compared to its III-V counterparts; therefore, it is promising for potential use in magnetooptical devices. 2 Dietl et al 3 first predicted room temperature ferromagnetism for ZnO containing 5% of Mn and a high hole concentration (3.5ϫ10 19 cm Ϫ3 ). Numerous reports on the ferromagnetism of TM-doped ZnO have emerged ever since.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported the absence of ferromagnetism in Mn 2 :ZnO at any temperature [8], but others have reported ferromagnetism with T C below room temperature [9]. Following the first claim of weak roomtemperature ferromagnetism in Mn 2 :ZnO [ferromagnetic saturation moment of M S (300 K) 0:16 B =Mn 2 ] [10], ferromagnetism was observed in Mn 2 :ZnO films grown on GaAs annealed above 500 C that appeared to correlate with the development of p-type conductivity [11], but ferromagnetism near room temperature was also claimed for n-type Mn 2 :ZnO [12].…”
mentioning
confidence: 99%
“…>300-350K [29,30] --->300K [30,32] 2 K [83] -4 (10) 2002 ---45K [33] >300K with Co [88] 550K with Cu [89] >350K [62,64] >300K with Fe [88] with Fe [89] 5 (10) 2003 --->r.t. [41] 37K [42] 70K [44] >250K [52] 225-300K [53 ] 250K with Sn [87] -225-300K [53] >350K [56] >r.t. [66,69] >350K with Li [90] --10 (17)…”
Section: Resultsmentioning
confidence: 99%